Examining the Intersectionality of Gender and Caste in Dalit Women’s Narratives - Singh, Ravindra Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
This review paper explores the intersectionality of gender and caste within Dalit women’s narratives, focusing on how these dual axes of oppression shape their lived experiences and representation in literature and oral histories. Drawing from seminal works by Dalit women writers such as Bama Faustina Soosairaj, Urmila Pawar, and Sivakami, the paper examines themes of systemic marginalization, resistance, and resilience. It critically analyzes how these narratives uniquely address patriarchy within caste systems and caste-based hierarchies within patriarchal structures, presenting a nuanced portrayal of Dalit women’s struggles and agency. By contextualizing these narratives within broader sociopolitical and historical frameworks, the paper highlights the contributions of Dalit women’s voices to feminist and anti-caste discourses in India. The review also identifies gaps in existing literature, such as the underrepresentation of intersectional perspectives in mainstream feminist and Dalit studies, advocating for a more inclusive approach to understanding the complexities of Dalit women’s identities. Ultimately, the paper underscores the transformative power of Dalit women’s narratives in challenging oppressive systems and reshaping academic and activist dialogues on caste and gender.